KONTRIBUSI KONSEP DIRI DAN PERHATIAN ORANG TUA TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X SMA DI KECAMATAN WERA BIMA - Dusalan Dusalan (SUPERMAT : Jurnal Pendidikan Matematika, 2017)
The purpose of this study is (1) Want to know how much the contribution of self-concept, and the attention of parents, to the results of mathematics learning in class X SMA in Wera Bima District; (2) Want to know how much the positive contribution of self-concept to the results of mathematics learning in class X SMA in Wera Bima District; and (3) Want to know how much the positive contribution of parents' attention to the results of mathematics learning in class X SMA in Wera Bima District. The type of this study was ex-post facto, the population in this study were Class X students of State High Schools in Wera Bima Subdistrict in the year 2017/2018 which were taken using Proportional stratified random sampling. Instruments used: (1) self-concept scale, (2) the scale of parental attention, (3) tests of mathematics learning outcomes. Data were analyzed by descriptive statistics and path analysis. The results of the study illustrate that; (1) Positive contribution to self-concept, and parents' attention together (simultaneous) to the mathematics learning outcomes of class X high school students in Wera Bima District, for R2square = 11.10%. (2) The positive contribution of self-concept towards the mathematics learning outcomes of class X high school students in Wera Bima Subdistrict, amounting to 15.70%. and (3) The positive contribution of parents' attention to the mathematics learning outcomes of class X high school students in Wera Bima District, amounting to 19.80%.